Work stress among nurse supervisors at Bangli Regional General Hospital: An analytical study - Yanti, Ni Putu Emy Darma; Devi , Agung Putu Ayu Mita Mahestya; Sanjiwani , Ida Arimurti; Krisnawati, Komang Menik Sri (Jurnal Keperawatan, 2026)
Introduction: Nurse supervisors play a critical role in healthcare, balancing direct patient care with administrative responsibilities. Their high-stress work environment increases the risk of physical and mental health challenges, which can negatively impact job performance. Identifying stressors and implementing effective interventions are essential to improving nurses’ well-being and maintaining high-quality patient care.Objectives: This study examines work-related stress levels among nurse supervisors at Bangli Regional General Hospital. Methods: Using a quantitative approach, data were collected from 99 participants selected through stratified random sampling. The New Brief Job Stress Questionnaire (BJSQ), a validated 63-item instrument, was used to assess stress levels, and data were analyzed using univariate methods. Results: Most nurse supervisors reported low stress levels, suggesting generally manageable workplace conditions. However, a notable proportion experienced moderate-to-severe stress, indicating the need for targeted support. Key stressors likely include high workloads, emotional demands, and insufficient rewards or recognition. To address these concerns, hospitals should enhance communication between staff and management to ensure nurses feel heard and supported. Additionally, improving reward systems—such as performance-based incentives or recognition programs—could boost morale and reduce burnout. Conclusions: Regular stress screenings should also be implemented to identify at-risk individuals early. By adopting these measures, healthcare institutions can foster a healthier work environment, ultimately benefiting both nurses and patient care outcomes. Further research could explore specific stress triggers and evaluate the effectiveness of workplace interventions.